2017
DOI: 10.3102/0162373717690830
|View full text |Cite
|
Sign up to set email alerts
|

Does Attending a Charter School Reduce the Likelihood of Being Placed Into Special Education? Evidence From Denver, Colorado

Abstract: We use administrative data to measure whether attending a charter school in Denver, Colorado, reduces the likelihood that students are newly classified as having a disability in primary grades. We employ an observational approach that takes advantage of Denver's Common Enrollment System, which allows us to observe each school that the student listed a preference to attend. We find evidence that attending a Denver charter school reduces the likelihood that a student is classified as having a specific learning d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…Barnard‐Brak et al () found significantly fewer pupils with disabilities in charter schools, at the national and state level. Winters et al () showed that charter schools, compared to district schools, reduced the classification of disability in Denver primary‐aged children; but mostly for learning disability (a high‐incidence, and sometimes contested, category) and not autism or speech or language disability (often seen to have more objective classification criteria). This might be related to our findings about the differences between SEN Support and EHC Plans in England.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barnard‐Brak et al () found significantly fewer pupils with disabilities in charter schools, at the national and state level. Winters et al () showed that charter schools, compared to district schools, reduced the classification of disability in Denver primary‐aged children; but mostly for learning disability (a high‐incidence, and sometimes contested, category) and not autism or speech or language disability (often seen to have more objective classification criteria). This might be related to our findings about the differences between SEN Support and EHC Plans in England.…”
Section: Discussionmentioning
confidence: 99%
“…Setren () suggested that charter schools may prefer not to identify marginal pupils as learning disabled, offering instead intensive tutoring to help pupils catch up academically. Both Winters et al () and Setren () found that pupils’ enrolment in charter schools reduces the probability of being classified into special education, whereas Tuchman and Wolf () found no supporting evidence of significant reclassification at intake in Louisiana’s private schools.…”
Section: School Autonomy Academic Performance and Educational Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since decentralization also reduces government control over the social goals of education, including equity for and support of local families, a focus on high-risk populations, as well as average effects, is important (Carnoy et al, 2005; Parry, 1997). Our study adds to a small but growing body of literature that focuses on the supply of education services in districts with a large number of charter schools (e.g., Arce-Trigatti, Harris, Jabbar, & Lincove, 2015; Winters, 2015; Winters, Carpenter, & Clayton, 2017), how school leaders make decisions about providing services in competitive environments (e.g., Jabbar, 2015a, 2015b), and the implications of both for students in school districts with market-based reforms. Studies by Winters (2015) and Winters et al (2017) focus on mandatory educational services for special education students and find important differences in how charter schools identify students for special education services.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…This compares to 14 percent and 5 percent respectively for the median public school in Florida. Recent evidence indicates this enrollment gap is explained by the combination of a lower baseline probability to apply and a reduced likelihood of special education classification in charter schools (Winters 2015;Winters, Carpenter, and Clayton 2017;Setren 2018).…”
Section: A Charter Schooling In Floridamentioning
confidence: 99%